Answer:
Irrational
Step-by-step explanation:
The square root of 16.45 would be a number that will never end, making it irrational.
Answer:
20 is the greatest common denominator. You can find this by listing the factors of each number. The highest number that can fit into both individual numbers is the common denominator. Since 40 is just 20 doubled, and 20 is just 20 once, it fits into both numbers and is also the highest number that can fit.
![\boxed{(x - a)(x - b) = 0}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%28x%20-%20a%29%28x%20-%20b%29%20%3D%200%7D)
The equation above is the intercept form. Both a-term and b-term are the roots of equation.
![x = - \frac{1}{3} \\ x = 5](https://tex.z-dn.net/?f=x%20%3D%20%20-%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%5C%5C%20x%20%3D%205)
These are the roots of equation. Therefore we substitute a = - 1/3 and b = 5 in the equation.
![(x + \frac{1}{3} )(x - 5) = 0](https://tex.z-dn.net/?f=%28x%20%2B%20%20%5Cfrac%7B1%7D%7B3%7D%20%29%28x%20-%20%205%29%20%3D%200)
Here we can convert the expression x+1/3 to this.
![x + \frac{1}{3} = 0 \\ 3x + 1 = 0](https://tex.z-dn.net/?f=x%20%2B%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%3D%200%20%5C%5C%20%203x%20%2B%201%20%3D%200)
Rewrite the equation.
![(3x + 1)(x - 5) = 0](https://tex.z-dn.net/?f=%283x%20%2B%201%29%28x%20-%205%29%20%3D%200)
Simplify by multiplying both expressions.
![3 {x}^{2} - 15x + x - 5 = 0 \\ 3 {x}^{2} - 14x - 5 = 0](https://tex.z-dn.net/?f=3%20%7Bx%7D%5E%7B2%7D%20%20-%2015x%20%2B%20x%20-%205%20%3D%200%20%5C%5C%203%20%7Bx%7D%5E%7B2%7D%20%20-%2014x%20%20-%205%20%3D%200)
<u>Answer</u><u> </u><u>Check</u>
Substitute the given roots in the equation.
![3 {(5)}^{2} - 14(5) - 5 = 0 \\ 75 - 70 - 5 = 0 \\ 75 - 75 = 0 \\ 0 = 0](https://tex.z-dn.net/?f=3%20%7B%285%29%7D%5E%7B2%7D%20%20-%2014%285%29%20%20-%205%20%3D%200%20%5C%5C%2075%20-%2070%20-%205%20%3D%200%20%5C%5C%2075%20-%2075%20%3D%200%20%5C%5C%200%20%3D%200)
![3( - \frac{1}{3} )^{2} - 14( - \frac{1}{3}) - 5 = 0 \\ 3( \frac{1}{9} ) + \frac{14}{3} - 5 = 0 \\ \frac{1}{3} + \frac{14}{3} - \frac{15}{3} = 0 \\ \frac{15}{3} - \frac{15}{3} = 0 \\ 0 = 0](https://tex.z-dn.net/?f=3%28%20-%20%20%5Cfrac%7B1%7D%7B3%7D%20%29%5E%7B2%7D%20%20-%2014%28%20-%20%20%5Cfrac%7B1%7D%7B3%7D%29%20-%205%20%3D%200%20%5C%5C%203%28%20%5Cfrac%7B1%7D%7B9%7D%20%29%20%2B%20%20%5Cfrac%7B14%7D%7B3%7D%20%20-%205%20%3D%200%20%5C%5C%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%2B%20%20%5Cfrac%7B14%7D%7B3%7D%20%20-%20%20%5Cfrac%7B15%7D%7B3%7D%20%20%3D%200%20%5C%5C%20%20%5Cfrac%7B15%7D%7B3%7D%20%20-%20%20%5Cfrac%7B15%7D%7B3%7D%20%20%3D%200%20%5C%5C%200%20%3D%200)
The equation is true for both roots.
<u>Answer</u>
![\large \boxed {3 {x}^{2} - 14x - 5 = 0}](https://tex.z-dn.net/?f=%20%5Clarge%20%5Cboxed%20%7B3%20%7Bx%7D%5E%7B2%7D%20%20-%2014x%20-%205%20%3D%200%7D)
Answer:
see explanation
Step-by-step explanation:
Given
10 = 7 - m ( subtract 3 from both sides )
3 = - m ( multiply both sides by - 1 )
- 3 = m , or
m = - 3
As a check
Substitute m = - 3 into the right side of the equation and if equal to the left side then it is the solution
7 - m = 7 - (- 3) = 7 + 3 = 10 = left side
Thus m = - 3 is the solution to the equation
The answer is eighty one over four